SELF-ESTEEM AS A CORRELATE OF SECONDARY SCHOOL STUDENTS’ SOCIAL ADJUSTMENT IN ENUGU STATE (Journal of Guidance and Counselling Studies, 2023)
This study investigated the relationship between self-esteem and secondary school students’ social adjustment in Enugu State. Three research questions guided the study and one null hypothesis was tested at 0.05 level of significance. Correlation research design was adopted for the study. The population for this study consisted of 17,861 senior secondary school (SS2) students. Research sample consisted of 1,824 students drawn through multi-stage sampling procedure. The instruments used for the study were Hare Self-esteem Scale (HSS) with a reliability coefficient alpha of 0.83, and Social Adjustment Scale (SAS) with a reliability coefficient alpha of 0.90. Descriptive statistics and Pearson Product Moment Correlation were used for data analysis. Results obtained from the study indicated that majority of the students in Enugu state have high self-esteem. The results also showed that majority of the students are socially adjusted. Moreso, the result revealed a very high positive significant relationship between students’ self-esteem and their social adjustment. The study concluded, among others that secondary school students’ self-esteem is related to their social adjustment. It was recommended, among others that counsellors should provide both group and individual counselling services to boost students’ self-esteem. This will help students to relate cordially with their peers, teachers, parents and other people around them.